2010
DOI: 10.1097/jto.0b013e3181c5e34f
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Postoperative Radiation after Esophagectomy for Esophageal Cancer

Abstract: This large population-based review supports the use of postoperative radiation for stage III SCC and AC of the esophagus. Given the retrospective nature of this study, until appropriately powered randomized trials confirm these results, caution should be used before broadly applying these findings in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 20 publications
1
58
1
Order By: Relevance
“…Several prospective randomized studies [1,2,3,5] demonstrated that PORT did not improve overall survival (OS) in thoracic esophageal squamous cell carcinoma (TESCC). Previously [4,6], we stratified patients by stage and lymph node metastasis, finding that PORT improved OS in lymph node-positive or stage III patients, which recent retrospective study findings support [7,8,9]. We also found that PORT reduced intrathoracic and supraclavicular recurrence.…”
Section: Introductionsupporting
confidence: 68%
See 2 more Smart Citations
“…Several prospective randomized studies [1,2,3,5] demonstrated that PORT did not improve overall survival (OS) in thoracic esophageal squamous cell carcinoma (TESCC). Previously [4,6], we stratified patients by stage and lymph node metastasis, finding that PORT improved OS in lymph node-positive or stage III patients, which recent retrospective study findings support [7,8,9]. We also found that PORT reduced intrathoracic and supraclavicular recurrence.…”
Section: Introductionsupporting
confidence: 68%
“…In our previous randomized study [4], we found that PORT improved OS and reduced locoregional recurrence. Other studies also reported the survival benefit of PORT in stage III or lymph node-positive ESCC patients [7,8,9]. However, the PORT methods for TESCC in all of the previously reported randomized clinical trials exclusively involved 2D techniques.…”
Section: Commentmentioning
confidence: 94%
See 1 more Smart Citation
“…Therefore, adjuvant radiotherapy and chemotherapy should be considered in these patients. Previous studies of typical esophageal SCC (Fok et al, 1993;Schreiber et al, 2010;Berger et al, 2011) have approved that adjuvant radiochemotherapy could decrease loco-regional recurrence and improve the long-term survival. Although such improvements were not observed in our study, the frequency of locoregional recurrence in patients without radiotherapy was significantly higher than for patients who received radiotherapy, showing that postoperative radiotherapy could reduce the locoregional recurrence rate.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal cancer is highly lethal with 11,650 (88.7%) estimated deaths among men and 2,850 (81.2%) among women. 2 Taken together with previous population studies, [3][4][5][6][7][8][9] the latter suggests a survival benefit for women when compared with men. The prevalence of the two main histologic subtypes-adenocarcinoma and squamous cell carcinoma-differs depending on geographic location.…”
Section: Introductionmentioning
confidence: 99%